2021
DOI: 10.15419/bmrat.v8i8.686
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesized monodispersed silver nanoparticles’ characterization and their efficacy against cancer cells

Abstract: Background: In biomedical research, silver nanoparticles have attracted the attention of many scientists in drug delivery and other applications. This study investigates the characterization of biologically synthesized nanoparticles and their efficacy on cancer cells. Methods: The characterization of biologically produced silver nanoparticles was accomplished using UV¬ visible absorption spectroscopy, which showed the maximum absorption at 422 nm. The structural morphology was carried out by transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In response to the PTAgNP treatment in the A431 cell line, the control cells emitted a low fluorescence signal while the PTAgNP treated cells exhibited a higher green fluorescent intensity, which indicates the overproduction of ROS. PTAgNPs trigger ROS, followed by oxidative stress; subsequently, the cells will respond by activating pro-inflammatory signaling cascades and inducing cell death by apoptosis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In response to the PTAgNP treatment in the A431 cell line, the control cells emitted a low fluorescence signal while the PTAgNP treated cells exhibited a higher green fluorescent intensity, which indicates the overproduction of ROS. PTAgNPs trigger ROS, followed by oxidative stress; subsequently, the cells will respond by activating pro-inflammatory signaling cascades and inducing cell death by apoptosis [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantages of TEM include the need for a large sample section and a high vacuum. Banu et al [240] reported to use TEM (Japanese JEM-3000 F, Jeol) to study the structural characterization of the AgNPs using drop-coated film and it showed spherical shape and 5 to 50 nm in size. Similarly, AgNPs was characterized using TEM and it revealed spherical shape with the size ranging from 13 to 40 nm [241].…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Nevertheless, their de ciencies prevail in requisition for gauze or adjuvants for use in a bleeding wound. Moreover, the ultra-moist environment propelled by HDG is not encouraging in wound mending promotion, as well as the scabbing effect, especially at earlier phase of wound formation [47].…”
Section: Wound Mending and Antibacterial Usesmentioning
confidence: 99%